PENGARUH PENGALAMAN, KEPERCAYAAN MEREK DAN LOKASI TERHADAP NIAT PEMBELIAN ULANG RUMAH SECARA ONLINE - Tobing, Damianna; Ruswanti, Endang (Politeknik Negeri Ambon, 2025)
Introduction: In today's digital era, the online experience has become a crucial factor influencing consumer purchasing decisions. This analyzes the impact of knowledge, brand trust, and location on the intention to repurchase homes online. A positive online shopping experience improves customer satisfaction and builds brand and e-commerce platform confidence. Strong brand trust reduces consumer concerns and enhances loyalty, while customer satisfaction drives the intention to repurchase. Methods: The research employed a quantitative survey using an online questionnaire distributed to 260 respondents who had made online home purchases. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Result: The results indicate that experience positively and significantly impacts customer satisfaction, which also positively influences the intention to repurchase. However, brand trust did not substantially affect the intention to repurchase, while the purchase location had a positive and significant impact. The conclusion of this study emphasizes the importance of a positive experience in enhancing satisfaction and the intention to repurchase. This research offers insights for companies to design strategies that enhance the consumer shopping experience, focusing on service convenience and purchase location. Keywords: Experience, Brand Trust, Location, Intention to Repurchase, Online Homes.